African descendencies in Iberian troubadourism (Práxis Educativa, 2022)
From bibliographical research, with decolonial theoretical basis, it is sought to understand, in this paper, the emergence of the Troubadourism in Europe, specifically in the Iberian Peninsula, from intercontinental cultural relations, with emphasis on African Arabs, despite the artistic manifestations at the time having ignored the presence of Africanities that contributed to the poetic orality. Therefore, the objective is to verify the presence of African descendencies in the Iberian Troubadourism. The undestanding of Troubadourism is historically defined in four theories: Middle Latin, liturgical, folkloric and Arabic (LAPA, 1973; SPINA, 1972). In general terms, the reflections of Canclini (2000), Glissant (2005) and Moore (2012) in the analysis of the text reveal the cultural intersections, called classic, popular and massive, taking into account that such definitions are not rigidly separated blocks, but rather borders among countries with different geography and customs in their territories. However, at certain times they share the same flowers, despite dividing them in their borders, and an epistemological racism that denied the African descendencies in their manifestations.Keywords: African descendency. Iberian Troubadourism. Poetic orality.